2008
DOI: 10.1063/1.2996028
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographically oriented Zn nanocrystals formed in ZnO by Mn+-implantation

Abstract: Articles you may be interested in Searching for room temperature ferromagnetism in transition metal implanted ZnO and GaN

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…22 It was found that the substitutional Mn concentration of ZnMnO nanorods was increased after treated with N 2 O plasma. 23,24 For hydrogenated Zn 0.95 Mn 0.05 O nanopowders, it is expected that the hydrogen treatment breaks the bonds between the Mn ions that are not located at the Zn sites and disperses the excess Mn into the Zn sites. 23 The vibration mode at 529 cm −1 can be considered to associate with the increment of doping Mn.…”
Section: Resultsmentioning
confidence: 99%
“…22 It was found that the substitutional Mn concentration of ZnMnO nanorods was increased after treated with N 2 O plasma. 23,24 For hydrogenated Zn 0.95 Mn 0.05 O nanopowders, it is expected that the hydrogen treatment breaks the bonds between the Mn ions that are not located at the Zn sites and disperses the excess Mn into the Zn sites. 23 The vibration mode at 529 cm −1 can be considered to associate with the increment of doping Mn.…”
Section: Resultsmentioning
confidence: 99%
“…Macroscopically, the appearance of Fe, Co, Ni is clearly revealed by x-ray absorption as shown later in Sec. III C. In literature the application of EELS in similar cases (embedded nanocrystals) is mainly for qualitative investigation 22,23,24 . On the other hand, exposing the nanocrystals to the electron beam for a longer time results in a heavy beam damage and contamination of the specimens, as well as the structural modification of the nanocrystals 25 .…”
Section: B Magnetic Propertiesmentioning
confidence: 99%
“…Apart from these normal modes of ZnO, there is an additional band with a peak at 526 cm -1 in the Raman spectra for all the Mn-doped ZnO films. Li et al [13] and Venkataraj et al…”
Section: Resultsmentioning
confidence: 99%